Electronic structure and bulk properties of MB₆ and MB₁₂ borides - Grechnev, G.E.; Baranovskiy, A.E.; Fil, V.D.; Ignatova, T.V.; Kolobov, I.G.; Logosha, A.V.; Shitsevalova, N.Yu.; Filippov, V.B.; Eriksson, O. (Физика низких температур, 2008)
Ab initio band structure calculations have been carried out for higher boridesMB6 andMB12. High precision
measurements of the elastic constants were performed for ZrB₁₂, HoB₁₂, ErB₁₂, TmB₁₂, LuB₁₂, YB₆
and LaB₆ compounds at low temperatures. The bulk properties of the borides have been analyzed on the basis
of the calculated equations of states and balanced crystal orbital overlap populations. Our calculations indicate
that hexaborides with divalent metals, CaB₆, SrB₆, BaB₆, and YbB₆, are semiconductors with small
energy gaps. The metallic MB6 hexaborides with trivalent M atoms are found to possess larger bulk moduli
values. For dodecaborides bulk moduli are found to be higher for MB₁₂ with increased filling of the conduction
band (ZrB₁₂, HfB₁₂, UB₁₂), comparatively to M³+B₁₂ compounds. The total energy calculations for different
magnetic configurations in YbB₁₂ point to a possibility of antiferromagnetic coupling between Yb³⁺
ions.